Palladium complexes bearing bis-aldimine N^C^N and N^N^N pincer ligands; A study of homogeneous/heterogeneous catalyzed CO2 hydrogenation - Nonkululeko Miya; Nyasha Makuve; Edward Ocansey; Gift Mehlana; James Darkwa; Banothile C.E. Makhubela (Elsevier, 2022)
Widespread consumption of fossil resources yielding waste CO2 has reached an all-time high and this poses an environmental threat that is contributing to global warming and climate change. Using CO2 as a C1 source may serve as an avenue to convert waste to valuable platform chemicals such as formates. In this contribution, we report on the design and synthesis of new pincer Pd(II) N^C^N and N^N^N complexes. Herein, we investigate the role of an N^C^N or N^N^N ligand backbone in Pd(II) pre-catalysts and the corresponding catalytic activity in CO2 hydrogenation. Catalytic activity and selectivity with TON (turnover number) up to 537, in a THF/H2O biphasic (affording catalyst separation) system, was achieved. The CO2-to-CH3OH conversion sequence in the presence of an amine using these Pd pincer catalysts is also investigated.